Analisis Penerapan Kebijakan Rescheduling sebagai Upaya Penyelesaian Kredit Bermasalah pada Koperasi Kopdit Pintu Air Cabang Bola - Maria Yerista Mindiyati; Yosefina Andia Dekrita; Fransiscus De Romario (International Forum of Researchers and Lecturers, 2024)
Branch Watergate Cooperative This study aims to determine the Application of Rescheduling Policy as an Effort to Resolve Non-Performing Loans at the Bola Branch Watergate Cooperative. The data collection techniques used were observation, interviews and documentation. The data analysis technique used is qualitative analysis, namely data collection and analysis, data reduction, data presentation, and verification or conclusions. The results of this study show that the causes of non-performing loans are: internal factors include: Less selective cooperatives in the analysis of credit, Lack of survey processes and the existence of family relationships. . External factors include mental factors, economic factors seen from the low income of members, member errors in calculating and not understanding well the business made so that they experience failure in managing the business, members are tempted by 3 times the share loan, and lack of communication. The implementation of rescheduling policy as an effort to resolve non-performing loans has gone well and meets the criteria. The rescheduling process was successful because most members were able to pay off the loan.